Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik Pada Materi Usaha dan Energi - Izzatul Muna Aulia; Hikmawati; Susilawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to examine the effect of the problem-based learning model on students’ physics problem-solving abilities on work and energy materials. The type of research used a quasi-experimental research design with a nonequivalent control group design. The population of this study was students of class X SMA Negeri 1 Empang for the 2021/2022 Academic Year. The research sample was taken using the cluster random sampling technique so that 27 students of class X IPA 2 were selected as the experimental class and 26 students of class X IPA 4 were selected as the control class. The experimental class was given treatment in the form of learning using a problem-based learning model, while the control class used a conventional model. The instrument used to measure the problem-solving ability of students was a description test which is first tested for the validity, reliability, different capability, and difficulty of question level. The result obtained in the form of the average value of KPM obtained by the two classes in the pre-test was the experimental class of 15,48 and the control class of 13,38 and the average value of KPM obtained by the two classes in the post-test was the experimental class of 88,81 and the control class of 80,73. The result of the data analysis test showed that the pre-test and post-test data were homogeneous and the post-test data were normally distributed and the hypothesis test they were analyzed using the t-test in order to obtain the value of 3,15. The value at a significant level of 5% is 2,007, then the value is bigger then. Thus, it is concluded that there is a positive effect of the problem-based learning model on students' physics problem-solving ability in the matter of work and energy.